2020
DOI: 10.3390/wevj11010020
|View full text |Cite
|
Sign up to set email alerts
|

Moving a Taxi Sector to Become Electric: Characterizing Taxi Drivers Interested in Purchasing a Full Electric Vehicle

Abstract: Electrification of mobility exceeds personal transport to increasingly focus on particular segments such as city logistics and taxis. These commercial mobility segments have different motives to purchase a full electric vehicle and require a particular approach to incentivize and facilitate the transition towards electric mobility. A case where a municipality was successful in stimulating the transition to electric mobility is the taxi sector in the city of Amsterdam. Using results from a survey study (n = 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Public charging systems should at the minimum have an "intelligent metering system" (p. 4). Taxis are a significant segment targeted for electrification (and in some cities, such as Amsterdam, to be fully electric) with their specific demands due to long durations of service and short turn-around [63]. Slow charging stations are most common in European cities, but the amount of fast charging stations is rising.…”
Section: Electric Transport Vehiclesmentioning
confidence: 99%
“…Public charging systems should at the minimum have an "intelligent metering system" (p. 4). Taxis are a significant segment targeted for electrification (and in some cities, such as Amsterdam, to be fully electric) with their specific demands due to long durations of service and short turn-around [63]. Slow charging stations are most common in European cities, but the amount of fast charging stations is rising.…”
Section: Electric Transport Vehiclesmentioning
confidence: 99%
“…Likely to decrease (shorter sessions) No direct effect No direct effect Electricity use increases (short-term spike, kWh at location) Increases [62][63][64] No direct (local) effect…”
Section: Fast Chargersmentioning
confidence: 99%
“…Grants were more effective than tax returns, and preferential treatments (access to lanes) as well as sufficient infrastructure affected preferences in this study. Fast chargers are one of the indicated needs for Amsterdam-based cab drivers [64]. From a global perspective, Lieven found that freeway chargers are also crucial for personal drivers (independent of driving distances).…”
Section: No Direct Effect Expectedmentioning
confidence: 99%
See 1 more Smart Citation
“…Many taxi companies have decided to purchase electric or hybrid vehicles [7][8][9][10][11]. An example for many cities can be found in Amsterdam (The Netherlands), where a taxi company has decided to replace its entire fleet of vehicles with electric ones by 2025 [12]. The largest number of e-taxis is in Beijing, China [13,14].…”
Section: Introductionmentioning
confidence: 99%